FAKTOR YANG MEMPENGARUHI PERDAGANGAN ANTAR WILAYAH DI SUMATERA UTARA - Indra Maipita (Quantitative Economics Journal, 2013)
This study aims to analyze the factors that affect trade between regions in the province of North Sumatra. Agrerat demand model was developed to regional economic model using simultaneous equations. 2 SLS method (two stage least squares) is used to estimate the function of inter-regional trade, interprovincial and expo rt fun ctions b etween province s impo rt fun ction. The estimation  res ults indicate that the difference between the export price and the provincial transport costs have an influence on interprovincial trade balance, while the import price differences between provinces, other provinces income, revenue North Sumatra province, did not sign ificantly affect the balance of trade between provinces